RETHINKING PEDAGOGICAL SHIFT IN ESP TEACHING-LEARNING APPROACHES ACROSS CROSS- CULTURAL EDUCATION - Kemprai, Joycee; Neiletuonuo; Singh, Tayenjam Rajesh (International Journal of Research -GRANTHAALAYAH, 2026)
Ragamala paintings emerged in the 16th century as a visual representation of Indian classical music. These intricate artwork compositions depict ragas and raginis (female ragas), which are associated with particular melodies, time cycles, and moods. One significant element found in Ragamala paintings is the portrayal of music instruments. Ragamala paintings are a form of Indian miniature paintings that depict musical modes or ragas in a visual format. These paintings are known for their intricate detail and vibrant colors, capturing the essence of Indian classical music. One of the recurring elements in Ragamala paintings is the inclusion of string instruments, which play a significant role in portraying the mood and character of the musical raga. This research paper aims to explore the role of string instruments in Ragamala paintings, using a case study approach to examine specific examples and analyze their cultural and artistic significance.